ANALISIS TINGKAT PENGETAHUAN MAHASISWA PENDIDIKAN IPA TENTANG DAMPAK KONSUMSI JUNK FOOD DI UNIVERSITAS NEGERI MEDAN - Gabrie Tamahra Nainggolan; Indah Maysaroh Siagian; Rinda Annisa Fhutu Neva; Kezia Elmaesia Tarigan; Marlon Brando Hutahaean (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the understanding of science education students at Medan State University about junk food and its effects on health. The background of this study reflects the increasing consumption of fast food among students, which can lead to various health problems such as obesity, diabetes, heart disease, and metabolic disorders. This study used a descriptive quantitative approach with a cross-sectional design. A total of 30 participants selected through purposive sampling technique completed a questionnaire that tested their understanding of the characteristics of junk food and its health impacts. The results revealed that the majority of students had a good understanding of junk food (66.6%) and the effects of junk food consumption (80%). This finding indicates that a science education background has a significant influence on improving nutritional literacy among students. The results of the Chi-Square test showed a significant relationship between the level of understanding of junk food and knowledge about the effects of junk food consumption (p = 0.001), indicating that the higher the students' knowledge about junk food, the better their understanding of its health risks. However, there were still a small number of participants with low knowledge, so there is a need to strengthen nutrition education through more focused and structured campus programs. This research is expected to be a reference for educational institutions in designing teaching strategies to improve healthy consumption patterns among students.